Ketamine-assisted psychotherapy in adolescents with multiple psychiatric diagnoses - Wolfson, Philip E.; Andries, Julane; Ahlers, Daniel; Whippo, Melissa (Frontiers in Psychiatry, 2023)
Ketamine-assisted psychotherapy is a promising new treatment for a variety of mental disorders of adolescence. There is currently an adolescent mental health crisis, with a high prevalence of disorders, diagnostic complexity, and many adolescents failing to respond to conventional treatments. While there is strong evidence for the use of ketamine in adults for a variety of treatment-refractory mental illnesses, research in adolescents is in its early stages. Ketamine-assisted psychotherapy (KAP) has been described in adults with promising results and here we present the first published cases of the use of KAP in adolescents. The four cases include adolescents aged 14–19 at the initiation of treatment, each with a variety of comorbid diagnoses including treatment-resistant depression, bipolar disorder, eating disorders, anxiety, panic, and trauma-related symptoms. They each initially received sublingual ketamine, followed by sessions with intramuscular ketamine. Their courses varied, but each had symptomatic and functional improvements, and the treatment was well-tolerated. Subjective patient reports are included. Rapid resolution of symptomatology and suffering often occurs within months as the result of the application of KAP to adolescent psychiatric care but is not inevitable. Family involvement in the treatment process appears to be essential to success. The development of this modality may have a singularly positive impact that will expand the psychiatric toolbox and its healing potency.